Spreadable Spectacle in Digital Culture: Civic Expression, Fake News, and the Role of Media Literacies in "Post-Fact" Society. (April 2017) - Mihailidis, Paul; Viotty, Samantha
This article explores the phenomenon of spectacle in the lead up and immediate aftermath of the 2016 U.S. presidential election. Through the spread of misinformation, the appropriation of cultural iconography, and the willing engagement of mainstream media to perpetuate partisan and polarizing information, the proliferation of populist rhetoric, polarizing views, and vitriolic opinions spread. Revisiting the world of critical theorist Guy Debord, this article argues that the proliferation of citizen-drive spectacle is unique in its origination and perpetuation, and a direct result of an increasingly polarized and distrustful public spending an increasing amount of time in homophilous networks where contrarian views are few and far between. We apply the frame of spreadable media to explore how citizen expression online initiated, sustained, and expanded the media spectacle that pervaded the 2016 U.S. presidential election. The conclusion of this work argues that media literacies, as a popular response mechanism to help cultivate more critical consumers of media, must be repositioned to respond to an era of partisanship and distrust. We present a set of considerations for repositioning the literacies to focus on critique and creation of media in support of a common good, and that can respond meaningfully in an era of spreadability, connectivity, and spectacle.